England's Dissatisfactions and the Conservative Dilemma. (August 2016) - Jeffery, Charlie; Henderson, Ailsa; Scully, Roger; Wyn Jones, Richard
In the immediate aftermath of the Scottish independence referendum, Prime Minister David Cameron raised the 'English Question' by advocating English Votes for English Laws in the House of Commons. This article explains why. It uses findings from the 2014 Future of England Survey of attitudes to constitutional issues in England. It reveals a group of interlinked concerns in England: about the advantages Scotland is perceived to have in the UK Union, about the absence of institutional recognition of England in the UK political system, and about the European Union and immigration. It shows that these concerns are distinctively English, held in a broadly uniform way across England and held most strongly by people in England who identify themselves as English, and not British. These concerns, and their linkage to and by English identity, differentiate the supporters of different political parties. They are held least strongly by Labour and Liberal Democrat supporters, and more strongly by Conservative and, especially, UKIP supporters. Cameron's move on the English Question – and subsequent profiling of English issues in the 2015 UK general election – recognised a territorially distinctive electoral battleground in England on which the Conservatives are now competing with UKIP to articulate a new English nationalism, perhaps at the expense of the Conservative Party's unionist heritage.